Concreto protegido com pintura intumescente em altas temperaturas: avaliação de propriedades mecânicas - Machado, Leonardo Machado de (2021)
The concrete subjected to action of high temperatures suffers degradation of its mechanical properties like compressive strength and modolus of elasticity. Passive protection materials can be used as a way to minimize these deleterious effects of exposing concrete to high temperatures, because delayed the transfer of heat from the outside to the protected element. Passive protection materials can be used in revitalization works or with project errors, specifically when concrete coverage is insufficient. This study proposes as a technological alternative for these cases the use of fire intumescent coating as a passive protection material, already established in steel structures. The fire intumescent coating in high temperatures generates chemical reactions that originate a carbonized foam of high insulating performance. Therefore, in order to investigate the efficiency of this coating on concrete structures, this research evaluated the mechanical behavior of conventional strength concrete, in this case, 38,5 MPa, on high temperatures (300ºC, 500ºC e 700ºC) with fire intumescent coating, through compressive strength, modolus of elasticity and loss of mass after heating. Through the results obtained statistically in the research, it was concluded that the fire intumescent coating has a good performance like passive protection materials when applied on conventional strenght concrete. The thickness of fire intumescent coating also is a significant and greater thickness has best performance.